Do malignant cells sleep at night? - Cortés-Hernández, Luis Enrique; Eslami-S, Zahra; Dujon, Antoine M.; Giraudeau, Mathieu; Ujvari, Beata; Thomas, Frédéric; Alix-Panabières, Catherine (Genome Biology, 2020)
Biological rhythms regulate the biology of most, if not all living creatures, from whole organisms to their constitutive cells, their microbiota, and also parasites. Here, we present the hypothesis that internal and external ecological variations induced by biological cycles also influence or are exploited by cancer cells, especially by circulating tumor cells, the key players in the metastatic cascade. We then discuss the possible clinical implications of the effect of biological cycles on cancer progression, and how they could be exploited to improve and standardize methods used in the liquid biopsy field.